Development of Multiple Polymorphic Microsatellite Markers for Ceratina calcarata (Hymenoptera: Apidae) Using Genome-Wide Analysis - Shell, Wyatt A. (J Insect Sci, 2016)
The small carpenter bee, Ceratina calcarata (Robertson), is a widespread native pollinator across eastern North America. The behavioral ecology and nesting biology of C. calcarata has been relatively well-studied and the species is emerging as a model organism for both native pollinator and social evolution research. C. calcarata is subsocial: reproductively mature females provide extended maternal care to their brood. As such, studies of C. calcarata may also reveal patterns of relatedness and demography unique to primitively social Hymenoptera. Here, we present 21 microsatellite loci, isolated from the recently completed C. calcarata genome. Screening in 39 individuals across their distribution revealed that no loci were in linkage disequilibrium, nor did any deviate significantly from Hardy-Weinberg following sequential Bonferroni correction. Allele count ranged from 2 to 14, and observed and expected heterozygosities ranged from 0.08 to 0.82 (mean 0.47) and 0.26 to 0.88 (mean 0.56), respectively. These markers will enable studies of population-wide genetic structuring across C. calcarata’s distribution. Such tools will also allow for exploration of between and within-colony relatedness in this subsocial native pollinator.